A randomised controlled intervention study on prevention of work related skin problems among gut cleaners in swine slaughterhouses. Issue 9 (18th August 2005) - Flyvholm, M-A; Mygind, K; Sell, L; Jensen, A; Jepsen, K F
Abstract : Aims: To evaluate the effect of an intervention to reduce work related skin problems in gut cleaning departments in Danish swine slaughterhouses. The intervention consisted of an evidence based prevention programme and a documented method for implementation. Methods: Randomised controlled intervention study with a one year follow up. The intervention included educational activities and evidence based recommendations. The effect of the intervention was evaluated by telephone interviews using a standardised questionnaire based on the Nordic Occupational Skin Questionnaire (NOSQ-2002) with modified and additional questions on exposure, preventive measures, information, and discussions on prevention of skin problems, etc. Results: A total of 644 (87.5%) responded at the baseline interview and 622 (71.6%) at the one year follow up interview. A total of 495 participated in both interviews (67.3%). In the intervention departments the frequency of eczema on hands or forearms within the past three months at follow up was reduced significantly from 56.2% at baseline to 41.0% at follow up, while a slight non-significant increase was observed in the comparison departments (from 45.9% to 50.2%). The intervention activities resulted in more frequent use of protective gloves in general and the use of cotton gloves worn underneath rubber and plastic gloves. At follow up three times as many in the intervention departments used the recommended high fat skin care products introduced as part of the intervention activities. At follow up, discussion of skin problems was increased in the intervention group while no changes were observed in the comparison group. Conclusions: A significant 27% relative reduction of occupational eczema in a high risk group was feasible through implementation of an evidence based prevention programme.